2009
DOI: 10.1007/s10452-009-9267-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of snow depth on under-ice irradiance and growth of Aulacoseira baicalensis in Lake Baikal

Abstract: Lake Baikal freezes for 4-5 months eachyear; yet the planktonic diatoms that grow under the ice include some of the largest species found in freshwater. An important factor influencing their growth is the depth of snow. In this study, a population of Aulacoseira baicalensis developed where there was little or no snow on the ice but declined where there was 10 cm of snow, because 99% of the available light was attenuated. Culture studies of light response showed that A. baicalensis was adapted to relatively low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 18 publications
2
94
1
5
Order By: Relevance
“…The high turbulence and convective mixing in the lake keeps cells in suspension, even when the lake is frozen for 4-5 months each year (Kelley, 1997;Granin et al, 1999;Jewson et al, 2009). The stimulus for this study was a remarkably detailed investigation of the seasonal changes in A. baicalensis cell length and diameter from 1926 to 1928 by Skabichevsky (1929).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high turbulence and convective mixing in the lake keeps cells in suspension, even when the lake is frozen for 4-5 months each year (Kelley, 1997;Granin et al, 1999;Jewson et al, 2009). The stimulus for this study was a remarkably detailed investigation of the seasonal changes in A. baicalensis cell length and diameter from 1926 to 1928 by Skabichevsky (1929).…”
Section: Introductionmentioning
confidence: 99%
“…A major aim of this study was to follow size changes in one of the largest filamentous planktonic diatoms found in freshwater, Aulacoseira baicalensis (K. Meyer) Simonsen (Skabichevsky, 1929(Skabichevsky, , 1960Bondarenko et al, 2006;Popovskaya et al, 2002;Jewson et al, 2009) and investigate if the changes were related to mixing depth in Lake Baikal, the world's oldest and deepest lake (Kozhov, 1963;Kozhova & Izmest'eva, 1998). The high turbulence and convective mixing in the lake keeps cells in suspension, even when the lake is frozen for 4-5 months each year (Kelley, 1997;Granin et al, 1999;Jewson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Zebra mussels are still the dominant dreissenid species in Lake Simcoe (Ozersky et al 2011b), so it is possible that there is a release from grazing pressure by zebra mussels at colder temperatures, which may be related to the winter phytoplankton peaks seen here. Most studies do not examine under-ice phytoplankton dynamics because low temperatures and light limitation are assumed to control the production of phytoplankton in the winter (Jewson et al 2009); however, recent evidence from Lake Erie revealed a winter diatom bloom under-ice that was far greater than the subsequent springtime proliferation of phytoplankton (Twiss et al 2012). Although the mechanisms driving the bloom in Lake Erie are different than in the seasonally ice-covered Lake Simcoe, high Chl-a concentrations have also been found under ice in Lake Simcoe (R.L.…”
Section: Seasonal Changes In Phytoplankton Dynamicsmentioning
confidence: 99%
“…Under-ice Chl-a concentrations, unlike the open-water Chl-a, did not change over time. The lack of change in Chl-a during the winter could be caused by under-ice light limitation (Jewson et al 2009), which would increase the Chl-a content in phytoplankton cells. This could explain why the winter peak is more evident with the Chl-a datasets, than phytoplankton biovolumes alone.…”
Section: Seasonal Changes In Phytoplankton Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation